Perioperative transfusion analysis and blood ordering schedule update for total knee arthroplasty - Manjiao MA; Yuelun ZHANG; Lulu MA; Jia GAN; Yuguang HUANG; Xisheng WENG; Jin LIN; Jin JIN; Wenwei QIAN (Zhongguo shuxue zazhi, 2023)
Objective To investigate the perioperative rate of allogeneic red blood cell (RBC) transfusion in patients who underwent total knee arthroplasty (TKA) and its risk factors, and to identify its cross-match to transfusion ratio (C∶T ratio). Methods Anesthetic data of patients who underwent TKA from January 2014 to October 2019 in Peking Union Medical College Hospital were collected and analyzed retrospectively. Perioperative allogeneic RBC transfusion rate was calculated, and binary Logistic regression analysis was performed to identify its risk factors in these patients. The overall C∶T ratio was calculated and divided into subgroups based on surgery type and age group. Results The study enrolled 2 903 patients. The perioperative rate of allogeneic RBC transfusion in TKA patients was 10.9% (95% CI 9.8%~12.0%) and overall C∶T ratio was 5.6∶1. The independent risk factors leading to perioperative allogeneic RBC transfusion included advanced age(OR=1.025, 95% CI 1.009~1.042, P<0.01), preoperative hemoglobin level(OR=0.966, 95% CI 0.954~0.978, P<0.001), preoperative anemia(OR=3.543, 95% CI 2.052~6.119, P<0.001), hematological diseases(OR=6.462, 95% CI 2.479~16.841, P<0.001), bilateral surgery(OR=7.681, 95% CI 5.759~10.245, P<0.01) and revision surgery(OR=9.584, 95% CI 4.360~21.065, P<0.001). Conclusion The risk factors for perioperative allogeneic RBC transfusion in TKA patients included advanced age, preoperative low hemoglobin level, preoperative anemia, hematological diseases, bilateral surgery and revision surgery. Only type and screen tests are recommended if patients receiving unilateral primary TKA surgery are less than 75 years old without anemia and hematological diseases, while at least one to four units of blood should be cross-matched if patients are with preoperative anemia and hematological diseases or will receive bilateral and revision arthroplasty.